Penerapan Sanksi bagi Pedagang Kaki Lima yang Berjualan di Pinggir Jalan Raya Beringkit Mengwitani Kabupaten Badung - I Made Wira Manik Prayascita; Anak Agung Sagung Laksmi Dewi; Desak Gde Dwi Arini (Jurnal Analogi Hukum, 2019)
PKL problems are indeed difficult to solve, this is evidenced by the fact that there are still many street vendors who roam the roadside, say in Badung Regency precisely stricken by Jalan Raya Mengwitani, Mengwi District, Badung, almost along the road there are street vendors selling, even more in the afternoon the number of street vendors increased. The ability of street vendors to organize themselves is what makes researchers interested in conducting research into organizing by street vendors, so that they are able to organize themselves to deal with the pressures experienced. The formulation of the problem in this study are: 1) what is the arrangement of street vendors (PKL) who sell on the edge of the road that has a Circular Mengwitani Badung Regency? 2) What is the action of the Badung District Government in dealing with street vendors (PKL) who sell on the edge of the road that has Circular Mengwitani Badung Regency? The technique of collecting data is done by interviews and documentation. Data were then analyzed using qualitative descriptive analysis. The conclusions of this study are: 1) Arrangement of Street Vendors selling on the edge of the Circular Circular Highway in Badung Regency is regulated in Badung District Regulation Number 7 of 2016 concerning Public Order and Public Peace listed in Article 25 and Article 27. Under the control authority the street vendors are in the Regional Government. But in its implementation the Regent gave a mandate to other agencies namely the Order of Peace and the Badung District Civil Service Police Unit. In this case the Civil Service Police Unit was formed to enforce the Perda, 2) the action of the Badung Regency government in dealing with street vendors in Badung Regency who sell on the roadside by providing sanctions for administrative sanctions and criminal sanctions to violating street vendors. Administrative sanctions can be in the form of reprimand, written warning, revocation of permit, termination and / or demolition. While criminal sanctions in the form of imprisonment for a maximum of 3 (three) months or a maximum fine of Rp. 25,000,000 (twenty five million rupiah).